Study of Effectiveness and Analysis of Mathematical Equation used in Cryptographic Technique for Data Security - Bankar, Bhojrao (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
Abstract A cryptographic system can be defined as an implementation of cryptographic techniques and their associated infrastructure to provide information security services. A cryptosystem is also known as aÂ cipher system. The classical ciphers work by changing or shifting the plaintext as substitution (replacing each character with another), or by transposition (shuffling the characters from its place). In this paper, the cipher techniques like Substitution, Transposition has been discussed with its functioning and effectiveness on the data security.